The effect of organic surfactant for stabilizing engineered functional pharmaceutical biodegradable polymeric nanoparticles - Azman, Muhamad @ Muhamad Nor (Universiti Malaysia Perlis (UniMAP), 2022)
Access is limited to UniMAP community.